Comparative Examination of Phytonutrients and Antioxidant Activity of Commonly Consumed Nuts and Seeds Grown in Vietnam - Trang H. D. Nguyen; Danh C. Vu; Sophie Alvarez; Khoa D. Nguyen; Thuong L. T. Nguyen; Nguyen N. Tuan; Nguyen T. Minh-Nguyet; Le N. Tam; Thi L. Ho; Xuyen T. Vo (Horticulturae, 2022)
The aim of the present study was to determine the phenolics, carotenoids, B-vitamins, and antioxidant activity of nuts and seeds grown in Vietnam. The concentrations of carotenoids and B-vitamins may vary among the nuts and seeds. Watermelon seed contained the highest level of lutein while pumpkin seed was the β-carotene richest sample. Sachi inchi and sunflower seed comprised considerable levels of vitamin B1, B6, and B9. The phenolic analysis revealed that cashew contained the highest total amount of flavonoids (466.04 μg/g), with catechin, epicatechin, and procyanidin B2 predominating over the other flavonoids. Likewise, chlorogenic and neochlorogenic acids made up the highest total amount of phenolic acids in sunflower seed (1870.41 μg/g). Walnut appeared to possess the highest antioxidant activity evaluated by DPPH, ABTS, FRAP, and reducing power assays. The correlation analysis indicated strong positive correlations between total phenolic content with DPPH and FRAP values. Principal component analysis graphically showed the distant positioning of cashew and sunflower seed, highlighting their significantly higher levels of phenolics. The findings of the study would be useful to improve nutrient database contents for flavonoids and phenolic acids as well as to promote the consumption of nut and seed products in Vietnam.